Identification of nitrous oxide generation in subsurface wastewater infiltration system filled with mixed matrix - Li, Ying-Hua; Yang, Lei; Li, Hai-Bo; Wang, Si-Qi; Su, Fei (Journal of Environmental Engineering and Landscape Management, 2020)
Subsurface wastewater infiltration systems (SWIS) are one of the important sources of nitrous oxide (N2O) production; understanding the biological processes and contributions of N2O will help control the amount of N2O produced. To quantitatively reveal the contribution of nitrification and denitrifiaction processes, 8 g potassium nitrate with 99.99 atom % 15N (i.e. 15N accounts for 99.99% of the total N) was dissolved in the influent (concentration: 3.3 g/L). Results showed that nitrification released more N2O within 0–12 h, accounting for 79.6 ± 2.4%. The denitrification process accounted for 88.5 ± 1.3% for N2O generation after the 12th hour. Thus, in order to effectively control the release of N2O, the denitrification process should be given more attention. The maximum release rate of N2O was 8.45 ± 0.8 mg/m2·h, which occurred near the end of the first wetting-drying cycle. Since then, peaks appeared periodically, mostly in the “rest” periods.